APPLICATION OF VIRTUAL AND AUGMENTED REALITY TECHNOLOGIES IN THE MODERN EDUCATION SYSTEM - Shyndaliyev Н.Т.; Kalkabayeva З.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article analyzes virtual and augmented reality technologies, one of the most widely used modern technologies at present. Virtual and augmented reality technologies have recently been used in medicine, architecture, manufacturing, and education. In this article, we will focus on the application of these technologies in the field of education. It is known that the use of new technologies in the educational process increases students ’ interest in classes. The use of digital technologies in education is the main achievement of the information society. However, creating a digital system for education using VR and AR technologies requires significant funds. At the beginning of the article, a brief overview of technologies is given, the main definitions are given, and the history is described. A review of the work of scientists conducting research in this area.